Developing New Marketing Strategy to Enhance Customer Loyalty at the Boarding House in Palembang City, South Sumatra - Alfandi, Muhammad Rifky; Siallagan, Manahan Parlindungan Saragih; Rahayu, Wulan Asti (Research Synergy Foundation, 2023)
The hospitality business is one of the world’s largest and fastest-growing industries, with many sub-sectors, such as hotels, restaurants, and resorts. However, some boarding houses in Palembang City, South Sumatra, are experiencing a shortage of monthly room occupants, particularly between August and December 2022. The objective of this study is to investigate whether it is brand image, customer satisfaction, or customer relationship management (CRM) that influences customer satisfaction and customer loyalty towards boarding house residents in Palembang City, South Sumatra, to control and increase the monthly room occupants, especially from August until December 2022. Hopefully, this issue will never happen again. The study uses quantitative methodology research to utilize a structural equation modeling approach using Partial Least Square. The study included 128 respondents undertaking activities in Palembang, South Sumatra, and staying in a boarding house. According to the findings of this study, brand image has a negative association with customer satisfaction, but service quality and customer relationship management (CRM) have a positive association with customer satisfaction. Furthermore, it was shown that customer satisfaction has a favorable association with customer loyalty. Consequently, if they wish to encourage customer satisfaction and customer loyalty to the boarding house, they must improve service quality and customer relationship management (CRM).